The development of an antibacterial assay and its use in the investigation of the combined effect of tetracycline and synthetic antimicrobial peptides on strains of Escherichia coli - Du Toit, Etienne Andre (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1999.